2020
DOI: 10.3389/fspas.2020.582564
|View full text |Cite
|
Sign up to set email alerts
|

The Compression of the Heliospheric Magnetic Structure by Interplanetary Shocks: Is the Structure at 1AU a Manifestation of Solar-Wind Turbulence or Is It Fossil Structure From the Sun?

Abstract: As a test of the action of MHD turbulence in the solar wind, the compression of the heliospheric magnetic structure at 1AU by 109 interplanetary shocks is examined. In the magnetic structure the orientations of solar-wind strong current sheets are statistically examined vs. time in the downstream plasmas after shock compression. If the current sheets of the solar wind are features of an active MHD turbulence, they should be destroyed and remade with isotropic orientations on the timescale of an eddy-turnover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…(Similarly, see Trenchi et al (2013a,b) for coherence indicated by energeticparticle observations). 3) Examination of the compression and rarefaction of the magnetic structure in the solar wind at 1 AU (Borovsky and Denton, 2016;Borovsky, 2020d) indicates that the current sheets and flux tubes are long lived (many 10 s of hours to the age of the solar-wind plasma). If the flux tubes of the solar wind were to be destroyed, two possible mechanisms for their destruction are turbulence and reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…(Similarly, see Trenchi et al (2013a,b) for coherence indicated by energeticparticle observations). 3) Examination of the compression and rarefaction of the magnetic structure in the solar wind at 1 AU (Borovsky and Denton, 2016;Borovsky, 2020d) indicates that the current sheets and flux tubes are long lived (many 10 s of hours to the age of the solar-wind plasma). If the flux tubes of the solar wind were to be destroyed, two possible mechanisms for their destruction are turbulence and reconnection.…”
Section: Introductionmentioning
confidence: 99%
“…These structures existed in the solar wind, injected at the time of solar wind formation, and were simply swept up with little evolution other than compression. Along these same lines, (Borovsky and Denton, 2010;Borovsky, 2020a) provided evidence that CIRs and interplanetary shocks are not regions of enhanced turbulence. Rather, turbulence measures changed steadily across CIRs, in correlation with source region changes from fast coronal hole wind to slower streamer belt wind.…”
Section: Importance Of Mesoscale Structures As Propagation Mediummentioning
confidence: 84%
“…Finally, a similar persisting anisotropy is measured when interplanetary shocks compress the solar-wind plasma (Borovsky, 2020a). The systematic anisotropy is difficult to measure using the average orientation of the current sheets because the direction of the compression is difficult to determine for the interplanetary shocks.…”
Section: Magnetic Structure Anisotropymentioning
confidence: 90%